Metaphorical Sense of the Gorga Toba Ornaments - Sihite, Jubilezer; Elfrida, Rotua; Simarmata, Rina Octavia; Manihuruk, Leonita (English Education Department, 2024)
Gorga is a carving art found on the exterior of Toba traditional houses with motifs consisting of three types of colors; red, black, and white. This article aims to reveal a very deep meaning in the carvings and colors of Gorga as the life principle of the Toba people. It is applied in public buildings, one of which is the art of building such as the Toba traditional house. The metaphorical approach has been applied to several building arts, but the clarity of the type of applied metaphor cannot be ascertained. The method uses qualitative, by describing the metaphorical elements of the results of the literature study and several references to design elements and the results on three study objects that have the same function as residential houses but different types. It was found that only two kinds of metaphor in the architecture are applied, they are tangible and intangible. Each element was compared in a matrix form so that it can be concluded that the elements contained in the metaphorical approach consist of meaning and form, and it is also concluded that the type of metaphor in each object of study has a different type of metaphor.